Makna dan Tradisi Prosesi Tujuh Bulanan Ibu Hamil Dalam Kehidupan Sosial Masyarakat Desa Tempapan Kuala, Kecamatan Galing, Kabupaten Sambas - Etriadi (Jurnal Ilmu Pendidikan dan Sosial, 2024)
This study aims to examine the meaning and tradition of the seven-month procession for pregnant women in the social life of the people of Tempapan Kuala Village, Galing Sub-district, Sambas Regency. The seven-month procession is part of a traditional ritual that is full of cultural values, religiosity, and social togetherness. This research used a qualitative approach with a descriptive method, where data was collected through in-depth interviews, participatory observation, and documentation studies. The results showed that the seven-month procession not only serves as a form of prayer and hope for the safety of the mother and fetus, but also strengthens social solidarity among community members. This tradition reflects a combination of Islamic values and local customs, which are implemented through various symbols and rituals, such as giving offerings, reciting prayers, and mutual cooperation in its implementation. In addition, the procession also serves as an informal educational tool for the younger generation on the importance of maintaining traditions and strengthening social relations. However, there are challenges in maintaining this tradition in the midst of modernization and social change. The findings contribute to understanding the role of local traditions in shaping cultural identity and strengthening social cohesion in rural communities. This study recommends the need for tradition preservation efforts through collaboration between traditional leaders, religious leaders, and the local government.